2018
DOI: 10.1016/j.scitotenv.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Explaining and modeling the concentration and loading of Escherichia coli in a stream—A case study

Abstract: Escherichia coli (E. coli) level in streams is a public health indicator. Therefore, being able to explain why E. coli levels are sometimes high and sometimes low is important. Using citizen science data from Fall Creek in central NY we found that complementarily using principal component analysis (PCA) and partial least squares (PLS) regression provided insights into the drivers of E. coli and a mechanism for predicting E. coli levels, respectively. We found that stormwater, temperature/season and shallow sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Wang et al . (2018) conducted a study modelling the abundance of E. coli in stream environments and found that nitrate/nitrite and phosphorous were good indicators of in‐stream E. coli levels. The usefulness of increased phosphorus levels as an indicator of faecal coliform proliferation in water and wetland environments has previously been reported by Toothman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . (2018) conducted a study modelling the abundance of E. coli in stream environments and found that nitrate/nitrite and phosphorous were good indicators of in‐stream E. coli levels. The usefulness of increased phosphorus levels as an indicator of faecal coliform proliferation in water and wetland environments has previously been reported by Toothman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Particles with an effective diameter of 1 nm to 10 μm are considered colloids (Chrysikopoulos & Sim, 1996; Gao, Cao, Dong, Luo, & Ma, 2011; Sirivithayapakorn & Keller, 2003a; Smith et al, 2007; Vasiliadou & Chrysikopoulos, 2011; Wan & Wilson, 1994b; Wang, Schneider, Parlange, Dahlke, & Walter, 2018). In the subsurface environment colloids comprise many naturally occurring substances including clays, metal oxides, mineral precipitates, and organic compounds as well as biological organisms such as pathogenic bacteria (Wang et al, 2017, 2018; Wang, Schneider, et al, 2018), viruses (Torkzaban, Hassanizadeh, Schijven, Bruijn, & Husman, 2006; Torkzaban, Hassanizadeh, Schijven, & van den Berg, 2006; Zhang, Hassanizadeh, Raoof, van Genuchten, & Roels, 2012), and protozoa (Bradford, Wang, Kim, Torkzaban, & Šimůnek, 2014; Sen, 2011). Many known environmental pollutants can attach to and move with colloids, a process referred to as colloid‐facilitated transport, which has been identified as one of the most important mechanisms responsible for the mobilization of reactive heavy metals in soils (Barton & Karathanasis, 2003; Gao et al, 2011; Grolimund & Borkovec, 2005; Kretzschmar & Schafer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Particles with an effective diameter of 1 nm to 10 μm are considered colloids (Chrysikopoulos & Sim, 1996;Gao, Cao, Dong, Luo, & Ma, 2011;Sirivithayapakorn & Keller, 2003a;Smith et al, 2007;Vasiliadou & Chrysikopoulos, 2011;Wan & Wilson, 1994b;Wang, Schneider, Parlange, Dahlke, & Walter, 2018). In the subsurface environment colloids comprise many naturally occurring substances including clays, metal oxides, mineral precipitates, and organic compounds as well as biological organisms such as pathogenic bacteria (Wang et al, 2017, viruses (Torkzaban, Hassanizadeh, Schijven, Bruijn, & Husman, 2006;Torkzaban, Hassanizadeh, Schijven, & van den Berg, 2006;Zhang, Hassanizadeh, Raoof, van Genuchten, & Roels, 2012), and protozoa (Bradford, Wang, Kim, Torkzaban, & Šimu ˚nek, 2014;Sen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the spatial and temporal variation of the microbial concentrations in freshwater sources and analyzed environmental factors that affect these variations. Wang et al (2018) found that stream flow conditions, temperature, and shallow subsurface flow were the dominant factors of temporal variation of the E. coli concentration in the stream. Tyner et al (2018) observed that distance from shore, wind speed, and recreational activity influenced spatial variation of the E. coli concentration in a lake.…”
mentioning
confidence: 96%